2015
DOI: 10.1111/iju.12863
|View full text |Cite
|
Sign up to set email alerts
|

Advances in sentinel node dissection in prostate cancer from a technical perspective

Abstract: Abbreviations & Acronyms ePLND = extended pelvic lymph node dissection FN = false negative ICG = indocyanine green LN = lymph node MRI = magnetic resonance imaging NIR = near-infrared NR = not reported PCa = prostate cancer PET = positron emission tomography PLND = pelvic lymph node dissection SN = sentinel node SPECT-CT = single-photon emission computed tomography combined with computed tomography TRUS = transrectal ultrasound Abstract: The most important feature of sentinel node biopsy for prostate cancer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 64 publications
0
30
0
2
Order By: Relevance
“…Since then a number of studies have investigated the utility of SLN mapping to guide PLND in prostate cancer and potentially reduce the extent of dissection, although the procedure is regarded as experimental at this stage 1 24. A recent review of the literature reported that SLNs were identified outside of the dissection template for an extended PLND in 4.1–25% of cases, and of patients with positive LNs 3.5–17% had SLN metastases outside of the extended PLND field 25. These findings highlight the potential for SLN mapping to improve nodal staging.…”
Section: Nodal Staging In Prostate Cancer and Patient Selection For Plndmentioning
confidence: 99%
“…Since then a number of studies have investigated the utility of SLN mapping to guide PLND in prostate cancer and potentially reduce the extent of dissection, although the procedure is regarded as experimental at this stage 1 24. A recent review of the literature reported that SLNs were identified outside of the dissection template for an extended PLND in 4.1–25% of cases, and of patients with positive LNs 3.5–17% had SLN metastases outside of the extended PLND field 25. These findings highlight the potential for SLN mapping to improve nodal staging.…”
Section: Nodal Staging In Prostate Cancer and Patient Selection For Plndmentioning
confidence: 99%
“…The median overall detection rate (C1 SLN in a patient) was 98.6 % for SPECT/CT and 85.3 % for planar scintigraphic imaging [28]. The role of preoperative 3D imaging in the most common cancer in men, prostate cancer, was recently summarized by Acar et al [29]. The detection rate of SPECT/CT ranged from 95.6 to 100 %, with the advantages of 3D imaging being most prominent in obese patients [29].…”
Section: Preoperative 3d Imaging (Spect/ct)mentioning
confidence: 99%
“…The role of preoperative 3D imaging in the most common cancer in men, prostate cancer, was recently summarized by Acar et al [29]. The detection rate of SPECT/CT ranged from 95.6 to 100 %, with the advantages of 3D imaging being most prominent in obese patients [29]. In a cohort of 46 patients with prostate cancer, Vermeeren et al reported that 44 % of metastatic SLNs were detected only by SPECT/CT, and not by planar imaging [30].…”
Section: Preoperative 3d Imaging (Spect/ct)mentioning
confidence: 99%
See 1 more Smart Citation
“…Is it possible to reduce further the percentage of LNI missing patients? The sentinel lymph node (SLN) technique, which assumes that the pathologic status of the SLN reflects the status of other pathologic regional lymph nodes, appears to be clinically robust in PC patients [10]. Nevertheless, the potential role of this technique in the decision tree to support prostate cancer patients is not yet well defined.…”
Section: Introductionmentioning
confidence: 99%